Impact of Gestational Diabetes Mellitus on Sexual Function: A Case-Control Study - Nunes, Sthefanie K. [UNESP]; Rudge, Cibele V C [UNESP]; Quiroz, Sofia C B V [UNESP]; Hallur, Raghavendra L. [UNESP]; Prudencio, Caroline B. [UNESP]; Pinheiro, Fabiane A. [UNESP]; Filho, Carlos I Sartorão [UNESP]; Odland, Jon; Calderon, Iracema M P [UNESP]; Barbosa, Angélica M P [UNESP]; Rudge, Marilza V C [UNESP] (SAGE Publications, 2020)
Background: The prevalence of gestational diabetes mellitus (GDM) is increasing worldwide, and this condition may be compromising female sexual function. However, there are controversial findings regarding the impact of GDM diagnosis and proposed treatments on sexual function during pregnancy. Therefore, this study seeks to elucidate the impact of GDM on sexual function in pregnant women by making a comparison between GDM and non-GDM groups using pregnancy sexual response inventory (PSRI). Materials and Methods: A case-control study involved 303 [168 women without GDM (control group) and 108 women diagnosed with GDM (case group)] Brazilian pregnant women at the Perinatal Diabetes Research Centre-Universidade Estadual Paulista, Brazil. PSRI was used to collect the data. The sexual function was scored in 10 domains as composite and specific scores by domains, categorized into quartiles (0 < 25 very low, 25 < 50 low, 50 < 75 high, and 75-100 very high), for before pregnancy and during pregnancy. The obtained data were subjected to statistical analysis using Student's t-, F-, and chi-square tests. Results: GDM women (PSRI composite score <50) are at risk of decreased sexual function during pregnancy, while non-GDM women are not at risk (PSRI composite score >50). There were no significant differences in the sexual functions between the two groups before pregnancy (p > 0.0001). After GDM diagnosis and proposed treatment, the differences were significant (p < 0.0001), notably in the frequency, arousal, orgasm, satisfaction, and dyspareunia score. Conclusions: This study showed that GDM diagnosis and proposed treatment resulted in decreased sexual functions during pregnancy.
Keywords: gestational diabetes mellitus; pregnancy; pregnancy sexual response inventory